(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The study was conducted on a three-year-old willow plantation, located on mineral soil of good rye complex, characterized by a low level of ground water. The aim of the study was to determine the reaction of two osier clones –Sprint and Boks –to fertilisa-tion with compost produced from city’s green waste. There were three combinations of fertilising used for the study: without compost fertilising, 10 and 12t ∙ ha of dry com-post. To perform the whole experiment, 100kg N, 80kg PO5and 100kg K2O5were used annually per 1ha. Cuttings were planted in the first decade of April 2010 with row spacing of 70cm, and 35cm space in a row. The detailed studies included: the number of sprouts on a plant, the thickness of sprouts at the height of 10cm from the soil surface, the length of sprouts and yields of raw dry and air-dry matter. The results revealed a positive effect of compost on the formation of the studied morphological characteristics of the sprouts and the yield of raw dry and air-dry matter. Both osier clones reacted similarly to the applied fertilising combinations, however the sprouts of Boks clone were distinguished by greater thickness and length.This clone was also prominent in terms of the size of produce.